Severe Pediatric Asthma Therapy: Mepolizumab - Nicola Ullmann; Francesca Peri; Francesca Peri; Olivia Florio; Olivia Florio; Federica Porcaro; Elisa Profeti; Alessandro Onofri; Renato Cutrera (Frontiers Media S.A., 2022)
There is a growing need for advanced treatment in children with persistent and severe asthma symptoms. As a matter of fact, between 2 and 5% of asthmatic children experience repeated hospitalizations and poor quality of life despite optimized treatment with inhaled glucocorticoid plus a second controller. In this scenario, mepolizumab, a humanized monoclonal antibody, has proven to be effective in controlling eosinophil proliferation by targeting interleukin-5 (IL-5), a key mediator of eosinophil activation pathways. Mepolizumab is approved since 2015 for adults at a monthly dose of 100 mg subcutaneously and it has been approved for patients ≥ 6 years of age in 2019. Especially in children aged 6 to 11 years, mepolizumab showed a greater bioavailability, with comparable pharmacodynamics parameters as in the adult population. The recommended dose of 40 mg every 4 weeks for children aged 6 through 11 years, and 100 mg for patients ≥ 12 years provides appropriate concentration and proved similar therapeutic effects as in the adult study group. A marked reduction in eosinophil counts clinically reflects a significant improvement in asthma control as demonstrated by validated questionnaires, reduction of exacerbation rates, and the number of hospitalizations. Finally, mepolizumab provides a safety and tolerability profile similar to that observed in adults with adverse events mostly of mild or moderate severity. The most common adverse events were headache and injection-site reaction. In conclusion, mepolizumab can be considered a safe and targeted step-up therapy for severe asthma with an eosinophilic phenotype in children and adolescents.